Metaphors, semiotics and futures studies. (November 2016) - Tarasti, Eero
Highlights: Semiotic theories of metaphors are presented. The problem of metaphors and future is scrutinized in light of existential semiotics. Futures studies and existential semiotics both concern the realm of possible worlds. Three kinds of transcendence are discussed: empirical, existential and radical. Abstract: Metaphor belongs to key concepts of semiotics. I have made my career in the field of semiotics and I appreciate the possibility to tell to the scientific community of futurists how a semiotician sees the various functions of metaphors and their connections to the future. The edited volume CLA 2.0 (Inayatullah & Milojevic, 2015 ) shows that in addition to metaphors, many futures researchers have found the general language-based approach of semiotics. The paper deals with three issues: first the theory of metaphors as such, much discussed in the semiotic literature; then what semiotics says about the future; and finally, what kind of semiotics we are considering here. I would propose to scrutinise the problem of metaphors and future in light of my own new theory which I call 'existential semiotics'.